A role for protein ubiquitination in VEGFR-2 signalling and angiogenesis. (19th November 2009) - Rahimi, Nader
Abstract : Regulation of angiogenesis is often viewed as a balance between pro-angiogenic and anti-angiogenic factors, and when the balance shifts in favour of angiogenesis stimulators, an angiogenic switch turns on the normally inactive endothelial cells to grow new blood vessels. Recent studies have shown that PLCγ1 (phospholipase Cγ1), a major signalling substrate of VEGFR-2 (vascular endothelial growth factor receptor 2), undergoes c-Cbl-mediated ubiquitination. c-Cbl suppresses tyrosine phosphorylation of PLCγ1 and with it VEGF (vascular endothelial growth factor)-induced endothelial cell proliferation and angiogenesis. Loss of c-Cbl in mice results in enhanced retinal neovascularization, VEGF- and tumour-induced angiogenesis. Notably, this observation suggests that c-Cbl-mediated ubiquitination pathway plays a central role in the 'angiogenic switch' employed by the VEGF system. The present article highlights the recent findings demonstrating a novel role for protein ubiquitination in angiogenesis and its potential in angiogenesis-based therapy.